Business cycle synchronisation at the regional level: evidence for the Portuguese regions - Correia, Leonida (2013)
This paper looks at the synchronisation of product per capita in Portuguese regions at a disaggregated level over the period 1988-2010. Furthermore, it examines the volatility of the regional cycles by calculating dispersion measures. As a whole, results indicate that in Portugal, despite the geographical proximity of regions, there are substantial regional asymmetries in the amplitude and degree of association of regional business cycles. The discrepancy in the dynamics of the average correlations of the NUTSIII cycle with the regional (NUTSII) and national cycles supports the existence of a regional border effect.